VEGETATIVE PHASE CHARACTERISTIC OF TABAH VARIETY OF BLACK RICE GROWN IN RED-YELLOW PODSOLIC SOIL COMBINE WITH ORGANIC MATERIALS - RAHMA YUNIARTI; Wasi'an Wasi'an; Tantri Palupi (Jurnal Sains Pertanian Equator, 2017)
The rice plant (Oryza sativa L.) is a rice-producing crop which is very important for the people of Indonesia, because most of the Indonesian population consuming rice as main food. Black rice contain a higher iron than white and brown rice. Black rice could increased body resistance to disease, improves liver cell damage, prevents kidney dysfunction, prevents cancer, slows aging, as antioxidants, cleans cholesterol in the blood and prevents anemia. The objective of this research was to obtain information on vegetative stage characteristics of black rice which treated with organic material on Red-Yellow Podsolic (RYP) soil. It also to understand the effect of organic material addition to the phenotypic phenotype phases of vegetative rice of black rice of Tabah variety. This study used a Completly Randomized Design (CRD) consisting of 6 levels i.e A = 0% (without inorganic), B = 100% cow compost, C = 75% cow compost + 25% Chicken manure, D = 50% cow compost + 50% Chicken manure, E = 25% cow compost + 75% chicken manure, F = 100% chicken manure. Each treatment consisted of 4 replications and each replication consisted of 4 samples. The study was conducted in experimental garden of Faculty of Agriculture, Tanjungpura University, Pontianak. This research obtained 13 character of Vegetative phases of black rice of Tabah. Qualititative characters of black rice at vegetative phase of of Tabah rice was not signivicantly different in all treatments. Various combinations of organic materials significantly affect the high character of seedlings, vegetative phase height, leaf length, leaf width and angle rods in black rice Stout.